Analisis Terhadap Bimbingan Perkawinan Pra Nikah Dalam Mewujudkan Keluarga Sakinah, Mawaddah wa Rohmah Di Kantor Kementerian Agama Kota Lubuklinggau - Sukatno, Sukatno; Yusefri, Yusefri; Sumarto, Sumarto (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2021)
In general, premarital marriage guidance is carried out by the District Office of Religious Affairs, but the reality is different from Lubuklinggau, the implementation of marriage guidance is carried out at the Ministry of Religion Office. In addition, divorce in Lubuklinggau is quite high, ranging from 1,200 cases. This research is a qualitative research with a field research method and uses a statute approach or a law approach. This study concludes that, firstly, premarital marriage guidance at the Ministry of Religious Affairs Office of Lubuklinggau City was held quite well, that the participants who were guided did not include the total number of prospective brides who registered at KUA because it adjusted the Budget Dipa/RKA-KL and there were no other policies. The implementation is flawed because many informants have not been educated. The divorce that occurred in Lubuklinggau may be caused by other factors such as economic factors, social factors and so on.